Şulman'ın Siyaset Bilimi Eleştirisi ve Hibrit Rejimler - Temi̇r, Erkam (Adem Yavuz SÖNMEZ, 2022)
The semi-autocratic and semi-democratic political regimes that started to emerge after the Cold War were called ‘hybrid regimes’. In the beginning, hybrid regimes were seen as a stage before the transition to full democracy. Although some hybrid regimes have democratized over the years, some have not changed at all, and even some of them have become more autocratic. Therefore, theories about hybrid regimes have started to evolve. In this article, Russian political scientist Ekaterina Mikhailovna Schulmann's views on political science criticism and hybrid regimes are discussed. Schulmann is shown among the most influential political scientists and most influential women in Russia. Schulmann’s ideas and observations on hybrid regimes are valuable as they offer an insider and original view. In fact, western theorists built the main lines in the formation of the concept. However, her approach went beyond being a local adaptation of the ideas of western theorists. Expanding the theoretical framework of the concept, Shulman developed the theory and established a balanced link between theory and truth. The article includes Schulmann's critique of political science. Her ideas about hybrid regimes are discussed. Issues such as the functioning of decision-making processes in hybrid regimes, how the power has changed hands, and the tendency of autocratization and democratization have been examined.

Tüm dünyada Soğuk Savaş sonrası ortaya çıkmaya başlayan yarı otokratik yarı demokratik siyasal rejimler ‘hibrit rejimler’ olarak adlandırılmıştır. Başlangıçta hibrit rejimler tam demokrasiye geçiş öncesindeki bir aşama olarak görülmüştür. Ancak yıllar içerisinde bazı hibrit rejimler demokratikleşmesine rağmen bazıları değişim göstermemiş, bir kısmı ise daha da otokratikleşmiştir. Bu nedenle hibrit rejimlerle ilgili teoriler de gelişmeye başlamıştır. Bu makalede Rus siyaset bilimci Yekaterina Mihaylovna Şulman’ın siyaset bilimi eleştirisi ve hibrit rejimlerle ilgili görüşleri ele alınmıştır. Rusya’nın en etkili siyaset bilimcileri ve en etkili kadınları arasında gösterilen Şulman’ın hibrit rejimler ile ilgili fikir ve tespitleri içeriden ve özgün bir bakış sunduğu için değerlidir. Nitekim hibrit rejim kavramının oluşumunda ana omurgayı batılı teorisyenler inşa etmiştir. Ancak Şulman’ın yaklaşımı batılı teorisyenlerin fikirlerinin yerel bir uyarlaması olmaktan öteye gitmiştir. Kavramanın kuramsal çerçevesini genişleten Şulman, teoriyi geliştirmiş, kuram ve hakikat arasında dengeli bir bağ kurmuştur. Makalede Şulman’ın siyaset bilimine eleştirisine yer verildikten sonra, hibrit rejimler ile ilgili fikirleri ele alınmış, hibrit rejimlerde karar alma süreçlerinin işleyişi, iktidarın ne şekilde el değiştirdiği, otokratikleşme ve demokratikleşme eğilimi gibi konular irdelenmiştir.
Keywords: Political Science; Decision-making; Hybrid regimes; Political science; Russia; Schulmann; Siyaset Bilimi; Hibrit rejimler; Karar alma; Rusya; Siyaset bilimi; Şulman; Decision-making; Hybrid regimes; Political science; Russia; Schulmann; 5. Gender equality; 16. Peace & justice